Cytotoxic effect of 1% and 3% Sodium hypochlorite as irrigation agent in primary teeth on human red blood cells: an in vitro study - Divya Mukundan; Maria Anthonet Sruthi (Romanian Journal of Stomatology)
Background and objectives. The endodontic treatment of primary teeth presents significant challenges due to their unique anatomical characteristics. To ensure a successful treatment, it is essential to evaluate a few factors. These factors include accurate diagnosis, disinfection protocol, intracanal medicaments, and irrigation solutions. While Sodium hypochlorite (NaOCl) has gained success as an irrigation agent in primary teeth, it is important to note that higher concentrations of NaOCl can potentially cause toxicity to the periapical environment if they pass through the tooth's apical foramina. Thus, this study compared the cytotoxicity of two different concentrations of sodium hypochlorite at varied volumes on red blood cells (RBC). Materials and methods. In order to evaluate the cytotoxicity potential, fresh human blood was collected from a single healthy individual and subjected to testing. For the test, 10 µL, 20 µL, 30 µL, 40 µL and 50 µL of 1% and 3% NaOCl were added to the RBC. The tubes were gently mixed and incubated at 37°C for 30 minutes. A UV-visible spectrophotometer was used to calculate the absorbance of the supernatant at a wavelength of 540 nm. Results. There was no significant difference in 1% sodium hypochlorite at different volumes with a p value >0.05 using Tukey's post hoc test. However, there was a significant difference between the volumes of 3% sodium hypochlorite at 40 and 50 µg/ml with a p value of 0.004 and 0.001 respectively. Conclusions. According to the current study's findings, 1% sodium hypochlorite solution exhibited less toxicity than 3% sodium hypochlorite.